Transformative effects of fluorescence imaging technologies on current vascular surgical practices: An updated review - Tao Fang; Jianxin Dong; Zhilei Xie (SLAS Technology)
Fluorescence imaging technologies have revolutionized vascular surgery by enabling real-time visualization of vascular anatomy, blood circulation, and tissue perfusion, thus improving intraoperative decision-making. This review provides a comprehensive analysis of key fluorescence modalities, including Fluorescence-Guided Surgery (FGS), Near-Infrared (NIR) fluorescence imaging, and Indocyanine Green (ICG) angiography, highlighting their roles in optimizing tissue perfusion assessment, vessel patency evaluation, and identifying anatomical variations. Unlike existing literature, this review addresses critical gaps in current practices by comparing these technologies and exploring their applications across a range of vascular procedures such as peripheral vascular surgery, coronary artery bypass grafting, and oncological operations. The review further delves into the potential future directions for fluorescence imaging in vascular surgery, emphasizing emerging technologies, challenges in clinical implementation, and how these advancements can enhance surgical precision, patient outcomes, and intraoperative guidance. By synthesizing the latest developments, this review offers valuable insights into the evolving role of fluorescence imaging in vascular surgery and its potential to transform surgical practices.